Approved Budget : Recurrent and capital estimates of the Government Nassarawa State, Nigeria for the 1997 fiscal year - Government Nassarawa State, Nigeria; Government of Nassarawa State, Nigeria (Lafia : Government Nassarawa State, Nigeria, 1997)
The volume consist of recurrent and capital estimates of the Government Nassarawa State, Nigeria for the 1997 fiscal year.
lje 19/3/2019
Arch
Keywords: Budget; Expenditures, Public; Nigeria